Stress assessment of argan (Argania spinosa (L.) Skeels) in response to land uses across an aridity gradient: Translational asymmetry and branch fractal dimension - Alados, C. L.; El Aich, A. (Journal of Arid Environments, 2008)
We used Translational Asymmetry (TA) of the annual stem, branch growth pattern and fractal dimension to quantify stress during development of argan (Argania spinosa (L.) Skeels) throughout its range in Morocco. Under communal grazing conditions known as ‘‘mouchaˆa’’ (Grazing Management), the branch fractal dimension was reduced and the TA of plants increased, reﬂecting the stressful conditions in which the argan trees were growing. Under Wild growing conditions, developmental instability increased as moisture decreased across a gradient of aridity. Under Barley Management conditions (barley crops are cultivated underneath of argan), argan increased branch complexity (branch fractal dimension) in the mildest area (Essaouira), which imposed an additional cost that results in increased TA. The results of the study best ﬁt the predictions that the level of asymmetry and fractal dimension reﬂects stressful conditions, which can be used to monitor the effect of environmental stress in the conservation of argan ecosystem.
Keywords: argan; aridity; developmental instability; environmental stress; fractal; Grazing; land use; translational asymmetry

HABITAT PREFERENCE OF SPANISH IBEX AND OTHER UNGULATES IN SIERRAS DE CAZORLA Y SEGURA (SPAIN) - ESCOS, J.; Alados, C. L. (MAMMALIA, 1992)
Studied the habitat preference in Autumn and Spring periods of Spanish ibex (Capra pyrenaica), fallow deer (Dama dama) and red deer (Cervus elaphus) in the Sierras de Cazorla y Segura Park (Spain). Spanish ibex occupied most altitude range studied, especially highest parts and avoiding areas below 800 m, red deer selected lowest elevations between 700 to 1100 m and fallow deer (between 1200-1600 m) occupied an intermediate annual altitudinal range. All the ungulates studied showed, except the red deer populations, a descent of altitudinal levels in the Spring period. Ibex used more covered areas specially females and young in Spring period, fallow deer occupied open habitats and red deer preferred holm-oak woods. In general terms the rut occurred in more open areas while in the birth season, females and young especially occupied covered areas. According to the overlap index (Pianka 1973) ibex with fallow deer could get a high risk of competition, while Spanish ibex and red deer, the only endemic species show the lowest level of overlapping on the resources studied. Segregation of the sexes studied in different habitats was observed. In Autumn, Spanish ibex and fallow deer showed a tendency to occupy sunny areas at dawn and dusk and this tendency occurred in red deer only at dawn but not at dusk. However in Spring, Spanish ibex, fallow and red deer occupied sunny slopes at dusk but only fallow deer do so at dawn.
The following values have no corresponding Zotero field: pub-location: 55 RUE DE BUFFON, 75005 PARIS, FRANCE publisher: MUSEUM NAT HIST NATURELLE
Keywords: APS; Capra pyrenaica; cervus elaphus; Dama dama; habitat prefference; Holm oak; Spain; ungulates